Classical and Variant Avian Infectious Bronchitis Virus Strains - Gary D. Butcher; David P. Shapiro; Richard D. Miles (EDIS, 2003)
Infectious bronchitis (IB) is an acute and highly contagious respiratory disease of chickens. The disease is characterized by respiratory signs including gasping, coughing, sneezing, tracheal râles, and nasal discharge. In young chickens, severe respiratory distress may occur. In layers, respiratory distress, decrease in egg production, and loss of internal egg quality and egg shell quality are reported. Some strains of the virus cause severe kidney damage and may be associated with high mortality. This document is VM127, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 1, 2002.